Gnomes of Gregory of Nazianzus as Part of Didactic Literature – an Inspirational Source of Homilies? - Koželová, Adriána Ingrid; Drengubiak, Ján (Vox Patrum, 2023)
The term didaktikos, first used by the ancient Greeks, referred to someone who was able to teach. However, not only in the sense of providing information and knowledge, but effectively conveying them so that they serve practical purposes. The aim of the contribution is to find out whether the gnomes of Gregory of Nazianzus formally meet the basic standards of didactic literature and thus to point out whether it is appropriate to use them as an inspirational source for writing sermons. By means of analytical and comparative method, we assess the presence of the basic features of homilies as well as whether they can be identified in the gnomes of Gregory of Nazianzus. The analysis confirms that homiletic texts are compatible with the gnomes by Gregory of Nazianzus and can be thus used as an inspirational source for writing sermons. Nazianzus’ gnomes – the subject of our research – are also interesting for the readers today and have a lot to offer. Even if it is unlikely that the poetry of Gregory of Nazianzus attracts broad readership, the sermon can be the tool that conveys the author’s moral legacy.